Reputation : - Fombrun, Charles J (Harvard Business School Press, 1996)
Good reputations, says Charles Fombrun, create wealth. In this thoroughly accessible book, Fombrun shows that by developing strong and consistent images, well-regarded companies generate hidden assets - or reputational capital - that give them a distinct advantage. Reputation examines how companies in a variety of industries, such as international fashion, investment banking, packaged goods, and even U.S. business schools, compete for prestige and achieve celebrity. Vital, relevant, and readable for professionals in public, community, investor, and employee relations as well as brand and marketing managers and senior executives.